2011
DOI: 10.1007/s00259-011-1739-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between infarct size and severity measured by gated SPECT and long-term left ventricular remodelling after acute myocardial infarction

Abstract: Purpose After acute myocardial infarction (AMI), left ventricular (LV) remodelling may occur despite successful reperfusion. This study aimed to investigate by gated single photon emission computed tomography (SPECT) the longterm evolution of myocardial perfusion and LV function after AMI and to identify the predictors of LV remodelling. Methods Sixty-eight AMI patients successfully treated by primary percutaneous coronary intervention underwent 99m Tc-sestamibi gated SPECT at 1 month (baseline) and over 6-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Besides that, PCSK9 has been demonstrated to be expressed in human atherosclerotic plaques [35] and the study investigated the relationship between PCSK9 genotypes/haplotypes and severity of coronary atherosclerosis elucidated a modest association between minimum lumen diameter tertiles and haplotype 3 [18]. Based on these findings, we tentatively speculated that plasma PCSK9 concentration may be related to the infarct size and severity, which were predicting factors for cardiac remodeling [36] and even cardiac dysfunction. As a result, we suspected that PCSK9 may be a biomarker for the prognosis of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, PCSK9 has been demonstrated to be expressed in human atherosclerotic plaques [35] and the study investigated the relationship between PCSK9 genotypes/haplotypes and severity of coronary atherosclerosis elucidated a modest association between minimum lumen diameter tertiles and haplotype 3 [18]. Based on these findings, we tentatively speculated that plasma PCSK9 concentration may be related to the infarct size and severity, which were predicting factors for cardiac remodeling [36] and even cardiac dysfunction. As a result, we suspected that PCSK9 may be a biomarker for the prognosis of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the IZ began to dilate and demonstrate an elevated fibre strain (Figures (a) and (b)). This explains the observations from recent studies , which found a higher risk of infarct expansion events in transmurally infarcted LVs. As our results demonstrated that localized highly abnormal stress at the BZ was a result of mechanical tethering following an overstretched IZ (Figure ), the magnitude of the maximum fibre stress recorded at both the sub‐endocardial and sub‐epicardial layers was also found to have a positive correlation with average IZ fibre strain (Figure (b)).…”
Section: Discussionmentioning
confidence: 99%
“…Rest perfusion imaging score 3-4, evaluated in a semi-quantitative scale by means of the gated SPECT myocardium, can be considered a correlate of non-viable myocardial tissue, and confirming a high rest summation score represents a strongly negative prognostic predictor 5,15,[20][21][22] . While comparing the perfusion and deformation analysis, the myocardium SPECT statistically achieved, probably as a result of attenuation artifacts in the territory of the right coronary artery corresponding to the localization of the LV inferior wall, a significantly lower accuracy in predicting segments with transmural scar, in comparison with the deformation analysis (AUC 0.822 vs. 0.866, P=0.036).…”
Section: Distinction Between Non-transmural and Transmural Infarctionmentioning
confidence: 99%